(untitled) (Perspectivas em Ciência da Informação, 2007)
The migration of documents to the digital format means deep change in the object to be preserved. Each fonds d’archives must be analyzed in its specificity, therefore no practical model is applicable generically. This work analyzes the migration of the archival collections of the Pierre Verger Foundation to digital format. The conclusion suggests that migration of documents needs the creation of web networks and compatible archival information systems to be successful.